Matching-adjusted indirect comparisons of safety and efficacy of acalabrutinib versus other targeted therapies in patients with treatment-naïve chronic lymphocytic leukemia. Issue 10 (24th August 2021) - Davids, Matthew S.; Telford, Claire; Abhyankar, Sarang; Waweru, Catherine; Ringshausen, Ingo
Abstract: Acalabrutinib is a highly selective, potent, next-generation, covalent Bruton tyrosine kinase inhibitor with minimal off-target activity. Matching-adjusted indirect comparisons (MAICs) were performed to estimate the safety and efficacy of acalabrutinib compared to other targeted therapies for treatment-naïve patients with chronic lymphocytic leukemia (CLL). Individual patient data for acalabrutinib (ELEVATE-TN trial) were matched to aggregate baseline characteristics for comparators. After matching, acalabrutinib (with or without obinutuzumab) showed improved safety outcomes, except for increased risk of neutropenia ( p  < 0.001) for acalabrutinib plus obinutuzumab versus ibrutinib and increased risk of leukopenia ( p  < 0.05) for acalabrutinib (with or without obinutuzumab) versus venetoclax plus obinutuzumab. There was no statistically significant difference in progression-free survival between acalabrutinib (with or without obinutuzumab) and any of the comparators. This MAIC demonstrated a favorable safety profile for acalabrutinib-based therapy compared with other targeted therapies in treatment-naïve patients with CLL, without compromising efficacy.